An 8 channel parallel transmit system with current sensor feedback for MRI-guided interventional applications. (1st November 2021) - Godinez, Felipe; Tomi-Tricot, Raphael; Quesson, Bruno; Barthel, Matthias; Lykowsky, Gunthard; Scott, Greig; Razavi, Reza; Hajnal, Joseph; Malik, Shaihan
Abstract: Background. Parallel transmit (pTx) has introduced many benefits to magnetic resonance imaging (MRI) with regard to decreased specific absorption rates and improved transmit field homogeneity, of particular importance in applications at higher magnetic field strengths. PTx has also been proposed as a solution to mitigating dangerous RF induced heating of elongated conductive devices such as those used in cardiac interventions. In this work we present a system that can augment a conventional scanner with pTx, in particular for use in interventional MRI for guidewire safety, by adjusting the amplitude and phase of each channel right before the start of the imaging pulses. Methods. The pTx system was designed to work in-line with a 1.5 T MRI while the RF synthesis and imaging control was maintained on the host MR scanner. The add-on pTx system relies on the RF transmit signal, unblanking pulse, and a protocol driven trigger from the scanner. The RF transmit was split into multiple fully modulated transmit signals to drive an array of custom transceiver coils. The performance of the 8-channel implementation was tested with regards to active and real-time control of RF induced currents on a standard guidewire, heating mitigation tests, and anatomical imaging in sheep. Results . The pTx system was intended to update RF shims in real-time and it was demonstrated that the safe RF shim could be determined while the guidewire is moved. The anatomical imaging demonstrated that cardiac anatomy and neighbouring superficial structures could be fully characterized with the pTx system inline. Conclusion. We have presented the design and performance of a real-time feedback control pTx system capable of adding such capabilities to a conventional MRI with the focus of guidewire imaging in cardiac interventional MRI applications.